PENGARUH INTERPERSONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Tarmizi, Achmad; Pentiyah, Dini (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this study was to determine the effect of interpersonal relations and work environment on job satisfaction of employees of the Supreme Court's Balitbang Secretariat of Education and Legal Training of the Supreme Court of the Republic of Indonesia (MA.RI). The method in this study uses quantitative, by distributing questionnaires to 50 employees. The analysis technique that the researcher uses in this study is a multiple linear regression analysis method. The results showed that interpersonal relationships and work environment had a close relationship seen from the R value of 0.588 or 58.8%. While the value of Adjusted R square is 0.318 or 31.8%. Changes in job satisfaction can be seen from interpersonal relationships and work environment, while the remaining 68.2% is due to other factors not examined in this study. Based on the results of the t test it is also known that interpersonal relationships and work environment partially have a positive and significant influence on job satisfaction. Keywords : interpersonal, work environtment, job satisfaction